2016
DOI: 10.1523/jneurosci.0236-16.2016
|View full text |Cite
|
Sign up to set email alerts
|

Shaping Intrinsic Neural Oscillations with Periodic Stimulation

Abstract: Rhythmic brain activity plays an important role in neural processing and behavior. Features of these oscillations, including amplitude, phase, and spectrum, can be influenced by internal states (e.g., shifts in arousal, attention or cognitive ability) or external stimulation. Electromagnetic stimulation techniques such as transcranial magnetic stimulation, transcranial direct current stimulation, and transcranial alternating current stimulation are used increasingly in both research and clinical settings. Curr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
154
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 145 publications
(174 citation statements)
references
References 56 publications
20
154
0
Order By: Relevance
“…Compared to corticospinal tracts, the sensory feedback pathways involve more synapses and interneurons. Computational studies based on neural mass and neural field models have demonstrated the nonlinear dynamics of thalamo-cortical system in the sensory pathway, showing similar nonlinearity as we detected in this study (Spiegler et al, 2011; Roberts and Robinson, 2012; Herrmann et al, 2016). Furthermore, the mechanoreceptors such as muscle spindles are also known to be highly nonlinear (Mileusnic et al, 2006).…”
Section: Discussionsupporting
confidence: 88%
“…Compared to corticospinal tracts, the sensory feedback pathways involve more synapses and interneurons. Computational studies based on neural mass and neural field models have demonstrated the nonlinear dynamics of thalamo-cortical system in the sensory pathway, showing similar nonlinearity as we detected in this study (Spiegler et al, 2011; Roberts and Robinson, 2012; Herrmann et al, 2016). Furthermore, the mechanoreceptors such as muscle spindles are also known to be highly nonlinear (Mileusnic et al, 2006).…”
Section: Discussionsupporting
confidence: 88%
“…Importantly, some studies have shown that the up-regulation of brain oscillations at target frequencies is more effective when the frequency of stimulation matches the natural rhythms, than when offset (see e.g. [32] for results in the human brain), which is in line with models of entrainment [42].…”
Section: Rhythmic Ntbs Interventions (And the Role Of Stimulation Frementioning
confidence: 57%
“…Ai & Ro, 2014;Lakatos, Karmos, Mehta, Ulbert, & Schroeder, 2008;Sherman et al, 2016) and may have other relationships with performance than the overall state as indexed here. Future investigations which directly manipulate ongoing oscillations through methods such as transcranial alternating current stimulation (Helfrich et al, 2014;Herrmann, Murray, Ionta, Hutt, & Lefebvre, 2016;Vosskuhl, Huster, & Herrmann, 2016) would help to answer these questions more directly.…”
Section: Discussionmentioning
confidence: 99%